The Relationship between Teacher Well-being, Spirituality, and Classroom Management Effectiveness in Madrasah Settings - Hanim, Siti Aisyah; Maulidawati, Maulidawati; Roziqi, Ahmad Khoirur (Yayasan Minang Darussalam, 2025)
This study explores the relationship between teacher well-being, spirituality, and classroom management effectiveness in madrasah settings. Teacher well-being has become an increasingly significant issue in contemporary educational research, as it is closely associated with motivation, job satisfaction, and professional performance. In Islamic educational institutions, spirituality is deeply embedded in teachers’ daily practices and plays a vital role in shaping their resilience, emotional balance, and pedagogical approach. Using a quantitative correlational design, this research investigates how teachers’ psychological and spiritual dimensions influence their ability to establish effective classroom management. Data were collected from madrasah teachers across different regions through structured questionnaires and analyzed using statistical techniques to determine correlations and predictive factors. The findings indicate that higher levels of teacher well-being and spirituality significantly contribute to improved classroom management effectiveness, creating a more positive and conducive learning environment. This study highlights the importance of integrating spiritual values and well-being strategies in professional development programs for madrasah teachers, ultimately enhancing both instructional quality and student outcomes.